RETOOLING FOR AN AGING AMERICA: REPORT IMPACT - Fulmer, T T (Innov Aging, 2018)
The 2008 Institute of Medicine report Retooling for an Aging America stated that “unless action is taken immediately, the health care workforce will lack the capacity (in both size and ability) to meet the needs of older patients in the future.” The committee set a target date of 2030 for their recommendations. The purpose of this presentation is to highlight the overall impact of the report’s recommendations upon the 10th anniversary of the report’s release, and to discuss where more effort is needed in order to realize the report’s vision.